The Use of Heritage in Serbia’s Foreign Policy: A Brief Overview of Past Practices and Advice for Further Development - Todorović, Miloš (Napredak, 2022)
Using theoretical frameworks of museology and heritology, such as the fact that cultural artefacts represent a source of information, this article analyzes the use of heritage in Serbia’s foreign policy through two case studies. Namely, the article offers an overview of some past practices, e.g. the state using Serbian medieval heritage in Kosovo and Metohija to prevent Kosovo from joining UNESCO in 2015, as well as actively using the Roman heritage to present Serbia as a part of the European discourse. The article also provides guidelines for potential further uses, i.e. practical advice on how to approach heritage and how to incorporate it most efficiently into Serbia’s cultural diplomacy and heritage diplomacy efforts, so as to achieve certain foreign policy goals.